The Satisfaction Level of Local Batam City Bus (Bimbar), Indonesia - Ahmad Mawardi Lubis; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
Public transportation has a significant role in urban life. One of the well-known public transportation in Batam City is the "Bimbar" City Bus. This research aims to get the satisfaction level of Bimbar users. The method used is data collection techniques using questionnaires, then the data obtained is processed using descriptive analysis techniques using the IPA (Importance Performance Analysis) method. As a result, the average gap between performance and importance is -0.96. The indicator with the highest gap is Cleanliness on city buses, with a value of -1.75, which means that service providers must prioritize their performance on Cleanliness on the bus so that users can feel satisfied. Another indicator that must be improved is adequate vehicle facilities and conditions because users still need to be satisfied with the performance of city bus service providers with relatively high gaps.